Significant gestures : a history of American Sign Language - Tabak, John. (Westport, Conn. : Praeger, 2006)
Looks at the history and development of American Sign Language.
Includes bibliographical references (p. [209]-217) and index.
Keywords: American Sign Language -- History; Deaf -- Means of communication -- United States; Deaf -- Education -- United States; Deafness -- United States